Assessment of knowledge, attitude and practice among community pharmacists towards dental care: A national cross sectional survey - Aline Hajj; Souheil Hallit; Christel Azzo; Frederic Abdou; Marwan Akel; Hala Sacre; Pascale Salameh; Lydia Rabbaa Khabbaz (Elsevier, 2019)
Background: Community pharmacists' contribution in health maintenance and promotion is significant but more studies are still needed to evaluate their role as healthcare providers. Objectives: Our primary objective was to assess knowledge, attitude, and practice among community pharmacists in Lebanon towards dental care. Secondary objectives included assessing the barriers to a good dental care practice and assess their educational needs for oral health counseling. Methods: A national cross-sectional study was carried out using an online questionnaire and targeting community pharmacists in Lebanon. Five, three and six questions were used to assess pharmacists' perceived knowledge, attitude and practice respectively. Stepwise linear regressions were conducted taking each time a different scale score as the dependent variable. Results: 497 (78.88%) pharmacists completed the survey (62% females). More than half (53.3%) exhibited good perceived knowledge, 39% a positive attitude and 47.3% a good practice regarding oral health. Pharmacists reported a good perceived knowledge regarding common oral conditions (good, very good and excellent knowledge: 73.2%). Most of the pharmacists (86.52%) perceived oral health promotion as an important part of their services. Moreover, 28.77% (n = 143) of pharmacists declared having difficulties in obtaining oral health information. The main barriers to a good practice included limited interaction between dentists and pharmacists and lack of training regarding oral health. The multivariable analyses showed a significant positive intercorrelation between perceived knowledge, attitude and practice. Working in the pharmacy for more than 40 h a week was associated with higher perceived knowledge (Beta = 2.846). Having a PhD degree was associated with lower practice scores (Beta = 3.676), whereas female gender was associated with lower practice scores (Beta = 2.334). Conclusions: Pharmacists have the overall required knowledge and attitude to play an important role in the patients' counseling towards dental care. Keywords: Attitude, Community pharmacists, Dental care, Oral health, Pharmacy practice